Penerapan Algoritma Base64 untuk Enkripsi dan Dekripsi File Gambar - Dominikus S Bani; Andreas Ariyanto Rangga; Dian Fransiska Ledi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Along with the development of the times, the use of information technology using computers as its media has increased rapidly. Indonesia is currently starting to adopt the concept of society 5.0 or what is known as Society 5.0, where this kind of activity focuses on community settings that are oriented towards IT-based human activities (Wijayanti et al., 2022). The application of the concept of